Renegades: Canadians in the Spanish Civil War - Hannant, Larry (Labour / Le Travail, 2009)
The article reviews the book, "Renegades: Canadians in the Spanish Civil War," by Michael Petrou.
Keywords: BOOKS – Reviews; CIVIL War; 1936-1939; History; Nonfiction; PETROU; Michael; RENEGADES: Canadians in the Spanish Civil War (Book); SPAIN